2008
DOI: 10.1002/bit.21987
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced differentiation of embryonic stem cells using co‐cultivation with hepatocytes

Abstract: We examined the effects of co-cultivated hepatocytes on the hepatospecific differentiation of murine embryonic stem (ES) cells. Utilizing an established mouse ES cell line expressing high or low levels of E-cadherin, that we have previously shown to be responsive to hepatotrophic growth factor stimulation (Dasgupta et al., 2005. Biotechnol Bioeng 92(3):257–266), we compared co-cultures of cadherin-expressing ES (CE-ES) cells with cultured rat hepatocytes, allowing for either paracrine interactions (indirect co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Several studies have examined the effects of E-cadherin on the differentiated function of ESCs [35][36][37]. In our lab, we have investigated how over-expressing E-cadherin in murine embryonic cells would affect hepatic differentiation in the presence of hepatotrophic growth factor stimulation [36], as well as coculture with primary rat hepatocytes [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the effects of E-cadherin on the differentiated function of ESCs [35][36][37]. In our lab, we have investigated how over-expressing E-cadherin in murine embryonic cells would affect hepatic differentiation in the presence of hepatotrophic growth factor stimulation [36], as well as coculture with primary rat hepatocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…In our lab, we have investigated how over-expressing E-cadherin in murine embryonic cells would affect hepatic differentiation in the presence of hepatotrophic growth factor stimulation [36], as well as coculture with primary rat hepatocytes [37]. Additionally, Karpowicz et al demonstrated the importance of E-cadherin adhesion for the differentiation of neural stem cells, as blocking E-cadherin adhesion using an antibody that targeted the extracellular domain of E-cadherin resulted in a reduction in both neuronal and astrocyte differentiation [15].…”
Section: Discussionmentioning
confidence: 99%
“…While the aforementioned co-culture systems utilize non-parenchymal cells or fetal liver cells as a support cell type, the use of hepatocytes as the feeder cell type in co-culture differentiation schemes has also been attempted. Moore et al examined the effects of cocultivated hepatocytes on the hepatospecific differentiation of murine ES cells [50]. Hepatocytes co-cultured with cadherin-expressing ES cells markedly enhanced ES cell differentiation toward the hepatic lineage, as demonstrated by hepatic-like cuboidal morphology, heightened gene expression of the late maturation marker G6P in relation to the early marker AFP, and the intracellular localization of albumin.…”
Section: Coculturementioning
confidence: 99%
“…In particular, the epithelial cadherin (E-cadherin) represents a key calcium-dependent cell adhesion molecule ensuring the integrity of epithelial tissues ( 4 ) . In conjunction with hepatotrophic factors, the E-cadherin signaling pathway promotes the onset of a hepatic phenotype and the maturation of embryonic stem cells ( 5,6 ) . In contrast to cell differentiation, the alteration of E-cadherin is frequently correlated with cancer progression as reported in numerous human tumors ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%